Prevalence of Temporomandibular Disorders Among Dental Students of College of Dentistry-Hawler Medical University. - Saeed Hameed Tutmayi; Twana Hoshyar Saleem; Sara Aswad Khoshnaw; Sana Khals Hamad; Sonya Nadir Saeed (Erbil Dental Journal)
Background: Temporomandibular disorders (TMD) are a group of conditions affecting the jaw joint and the muscles that control jaw movement, can cause pain and discomfort in the jaw, face, and neck, and affect a person's ability to speak, chew, and swallow.